The Clinical and Genetic Features in Chinese Children With Steroid-Resistant or Early-Onset Nephrotic Syndrome: A Multicenter Cohort Study - Zhu, Xiujuan; Zhang, Yanqin; Yu, Zihua; Yu, Li; Huang, Wenyan; Sun, Shuzhen; Li, Yingjie; Wang, Mo; Li, Yongzhen; Sun, Liangzhong; Yang, Qing; Deng, Fang; et al. (Frontiers in Medicine, 2022)
Steroid-resistant nephrotic syndrome (SRNS) is one of the major causes of end-stage kidney disease (ESKD) in children and young adults. For approximately 30% of children with SRNS results from a genetic cause. In this study, genotype-phenotype correlations in a cohort of 283 pediatric patients with SRNS or early-onset NS (nephrotic syndrome presenting within the first year of life) from 23 major pediatric nephrology centers in China were analyzed. All patients were performed with next-generation sequencing and Sanger sequencing. The overall mutation detection rate was 37.5% (106 of 283 patients). WT1 was the most frequently detected mutation, followed by NPHS1, NPHS2, and ADCK4, and these four major causative genes (WT1, NPHS1, NPHS2, and ADCK4) account for 73.6% of patients with monogenic SRNS. Thirteen of 106 individuals (12.3%) carried mutations in ADCK4 that function within the coenzyme Q10 biosynthesis pathway. In the higher frequently ADCK4-related SRNS, two mutations, c.737G>A (p.S246N) and c.748G>C (p.D250H), were the most prevalent. Our study provides not only definitive diagnosis but also facilitate available targeted treatment for SRNS, and prediction of prognosis and renal outcome. Our indications for genetic testing are patients with FSGS, initial SRNS, cases of positive family history or those with extra-renal manifestations.